Resiliensi remaja korban kekerasan seksual di Kabupaten Timor Tengah Selatan: Analisis Model Miles dan Huberman - Anjarima Devitri Kase; Dwi Sarwindah Sukiatni; Rahma Kusumandari (INNER: Journal of Psychological Research, 2023)
This research is a qualitative study aimed at understanding the depiction of resilience among adolescent victims of sexual violence in the South Central Timor Regency. The sampling technique employed in this study is purposive sampling, with three subjects selected. Data collection methods used in this research include observation, interviews, and documentation. The collected research data is analyzed using the data analysis techniques of Miles and Huberman, with triangulation employed to determine the credibility of the research data. Based on the research findings, it is observed that sources of resilience among sexual violence victims stem from aspects such as openness and support from individuals in their social environment, particularly parental openness and support, a desire for independence, access to necessary resources, a sense of self-responsibility, and problem-solving abilities to cope with and find solutions in difficult situations. Keywords: Resilience, Adolescents, Sexual Violence